2017
DOI: 10.2217/nmt-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Minimally Supervised Home Exercise and Walking Program for People With Parkinson’s Disease in Jordan

Abstract: A home exercise program was feasible. Sociocultural barriers specific to Arabic culture may affect the uptake of such an intervention in Parkinson's disease in these countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 38 publications
1
46
0
1
Order By: Relevance
“…For instance, Stallibrass et al (2002) using ABCT (44), Goodwin (2011) using an exercise intervention (45), and Sedaghati (2016) (31) using a selective corrective exercise showed improvements in trunk posture alignment. However, Sparrow using 3 months of active balance exercises (46) and Khalil using a homeexercise and walking program (47) revealed no significant differences in posture alignment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Stallibrass et al (2002) using ABCT (44), Goodwin (2011) using an exercise intervention (45), and Sedaghati (2016) (31) using a selective corrective exercise showed improvements in trunk posture alignment. However, Sparrow using 3 months of active balance exercises (46) and Khalil using a homeexercise and walking program (47) revealed no significant differences in posture alignment.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely mentioned in the literature that individual with PD have important barriers in adherence and motivation with regards to maintaining an active lifestyle [3, 5, 6]. However, few studies have sought practical changes to increase individual’s motivation and empowerment, most of which are qualitative [5, 11].…”
Section: Discussionmentioning
confidence: 99%
“…The global benefits of physical therapy in the domains of International Classification of Functioning, Disability and Health (ICF) [1] in activity, participation, and body structure and function for individuals with Parkinson’s disease (PD) have been clearly established in the literature [2, 3]. However, studies have shown that some individuals present with barriers to the practice of physical therapy, decreasing their motivation towards the treatment and consequently decreasing their adherence [46]. Among the strategies suggested both by PD individual’s and by the therapists to engage the individuals in the exercise, a joint work seeking to stimulate self-efficacy and confidence, recognizing and respecting their barriers and individual motivations, were considered of utmost importance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Details of the exercise DVD and its content are published elsewhere. [ 25 , 26 ] In brief, this DVD focuses on the main components of fitness introduced by an acting lady and a gentleman in 5 main sections. The first section is focused on warm up and flexibility activities; the second, third, and fourth sections focus on strength, flexibility, balance and endurance exercises, and training on performing functional tasks of sit to stand, stepping up onto stairs, and getting on and off the floor; and the fifth section focuses on relaxation, stretching, and breathing techniques.…”
Section: Methodsmentioning
confidence: 99%